Altered triglyceride glucose index and fasted serum triglyceride high‐density lipoprotein cholesterol ratio predict incidence of cardiovascular disease in the Mashhad cohort study. (19th January 2022) - Mirshafiei, Hassan; Darroudi, Susan; Ghayour‐Mobarhan, Majid; Esmaeili, Habibollah; AkbariRad, Mina; Mouhebati, Mohsen; Ferns, Gordon A.
Abstract: The triglyceride glucose (TyG) index and triglyceride/high lipoprotein density cholesterol (TG/HDL‐C) are two important risk markers to evaluate the insulin resistance and cardiovascular diseases (CVDs). To assess the association between TG/HDL‐C and TyG index and CVDs. The Mashhad stroke and heart association disorder cohort study started in 2010 and has been continued until 2020. During 6‐year follow‐up of 9704 participants, 235 events including 118 acute coronary syndrome (ACS), 83 chronic coronary syndrome, 27 myocardial infarction, and 27 cardiac death were confirmed. SPSS software (version 21) was used for statistical analysis and figures were drawn by GraphPad Prism 6 software. The prevalence of ACS and cardiac death were higher in the fourth quartile of serum TG/HDL‐C (>4.43) and higher prevalence of ACS was considered in subjects classified in the fourth quartile of TyG index (>8.98). A high TyG index was associated with an increased risk of ACS and cardiac death [1.362 (95% confidence interval [CI]: [1.013–1.831]) and 2.3 (95% CI: [1.247–4.241])] respectively; based on Cox regression analysis elevated TyG and TG/HDL‐C increased the chance of CVD by [1.634 (95% CI: 1.304–2.047) and 1.068 (95% CI: 1.031–1.105)], respectively. Our results strongly showed that TyG index and TG/HDL‐C are independent risk factors for incident CVD, suggesting that TyG index and TG/HDL‐C may be as an important unique biomarker for predicting CVD outcomes and progression.